2017
DOI: 10.1098/rsos.161009
|View full text |Cite
|
Sign up to set email alerts
|

Red fluorescence of the triplefinTripterygion delaisiis increasingly visible against background light with increasing depth

Abstract: The light environment in water bodies changes with depth due to the absorption of short and long wavelengths. Below 10 m depth, red wavelengths are almost completely absent rendering any red-reflecting animal dark and achromatic. However, fluorescence may produce red coloration even when red light is not available for reflection. A large number of marine taxa including over 270 fish species are known to produce red fluorescence, yet it is unclear under which natural light environment fluorescence contributes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 50 publications
3
47
0
Order By: Relevance
“…T. delaisi shows highest sensitivity in the green wavelength range [26]. The stenospectral treatment might therefore have been perceived brighter by the fish, regardless of the real overall brightness.…”
Section: Discussionmentioning
confidence: 99%
“…T. delaisi shows highest sensitivity in the green wavelength range [26]. The stenospectral treatment might therefore have been perceived brighter by the fish, regardless of the real overall brightness.…”
Section: Discussionmentioning
confidence: 99%
“…There are alternative ways to approach the measurement and modeling of fluorescence contribution (e.g., Bitton et al, 2017;Taboada et al, 2017). While these differ in detail from the approach described here they lead to the same end: an estimate of the contribution of fluorescence to the optical signal.…”
Section: Discussionmentioning
confidence: 99%
“…Arnold et al (2002) demonstrated all criteria for a fluorescence function in a bird (budgerigar, Melopsittacus undulatus), including a behavioral response. The quantitative approaches of Mazel et al (2004), Taboada et al (2017), and Bitton et al (2017) indicated the potential for fluorescence to play a visual role in a stomatopod (Lysiosquillina glabriuscula), frog (Hypsiboas punctatus) and fish (Trypterygion delaisi), respectively. Another quantitative treatment (Iriel and Lagorio, 2010) indicated that the fluorescence of the flowers investigated was too weak relative to reflected light to have a functional role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for the breeding season, when males develop prominent coloration, individuals are highly cryptic against their natural background, with no obvious sexual dimorphism. Tripterygion delaisi displays highly fluorescent irides with an average peak emission (λ max ) of 609 nm with a full width at half maximum range of 572 nm to 686 nm (Bitton et al, 2017). Furthermore, it can perceive its own red fluorescence (Bitton et al, 2017;Kalb, Schneider, Sprenger, & Michiels, 2015), which is regulated from nearly absent to maximum brightness through melanosome dispersal or aggregation in melanophores in less than 30 s (Wucherer & Michiels, 2014).…”
Section: Materials S and Me Thodsmentioning
confidence: 99%